Knowledge, attitude and practices among Healthcare Workers towards Pulmonary Plague Infection following an outbreak in Madagascar, 2017: A pilot study - Inessa Markus; Lynn Meurs; Rebekah Wood; Vaoary Razafimbia; Andrianasolo Radonirina; Delphin Kolie; Rapelerano Rabenja Fahafahantsoa; Alexandre Delamou; Jan Walter; Matthias Borchert; Thomas Paerisch (PLoS ONE, 2025)
Objectives To assess training needs of healthcare workers (HCWs) on pulmonary plague (PP) control after the large PP outbreak in Madagascar 2017. Methods In 2018, we conducted a knowledge, attitudes and practices (KAP) survey among HCWs (PP cases and comparison group) in Antananarivo and Toamasina. Proportions were calculated, differences between groups were tested for significance. Results Knowledge levels were similar for HCW PP cases and the HCW comparison group. Among 59 HCW over 90% named the distinctive disease forms of plague (bubonic (93%), pulmonary (98%)), and 72% the causative agent. Washing hands was mentioned as protective measure by 56%, while 93% reported to have always washed hands after performing medical procedures. Only 3.5% reported managed PP cases before the outbreak; 38% reported to have felt confident performing invasive procedures while caring for PP cases at the beginning versus 62% at the end of the outbreak. HCW who remained uninfected reported more often than PP cases to have worn multiple or single use medical coats ((93% vs. 53%, p = 0.001; 60% vs. 20%, p = 0.028), and less frequently to have paid for chemoprophylaxis out of pocket (11% versus 50%; p = 0.008). Conclusion Despite the good overall knowledge, specific knowledge gaps and the mismatch between knowledge and practice of basic hygiene measures and low confidence in providing care for PP cases after the outbreak indicate a persisting need for training.